2015
DOI: 10.1016/j.dnarep.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The R280H X-ray cross-complementing 1 germline variant induces genomic instability and cellular transformation

Abstract: X-ray Repair Cross Complementing protein 1 (XRCC1) plays an important role in base excision DNA repair (BER) as a scaffolding protein for BER enzymes. BER is one of the basic DNA repair pathways repairing greater than 20,000 endogenous lesions per cell per day. Proper functioning of XRCC1, one of the most important players in BER, was suggested to be indispensable for effective DNA repair. Despite accumulating evidence of an important role that XRCC1 plays in maintaining genomic stability, the relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Interestingly, in consistent with our findings that show a significant difference with R280H in comparison with all other XRCC1 variants tested in this study (Fig. 4D), it has been reported that polymorphic variant R280H exhibits a decreased retention time from the site of DNA damage induced single-stranded breaks (84,85). Furthermore, the amino acid substitutions within the central DNA binding domain (219-415 aa) encompassing the first BRCT domain of XRCC1 have been found to disrupt DNA binding in vitro and the recruitment of XRCC1 to near-UV micro-irradiated sites of the nuclei is strongly influenced by the region encompassing amino acids 166 to 310 without affecting its initial recruitment, suggesting that the DNA-binding activity of XRCC1 is crucial for efficient DNA damage repair (86).…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, in consistent with our findings that show a significant difference with R280H in comparison with all other XRCC1 variants tested in this study (Fig. 4D), it has been reported that polymorphic variant R280H exhibits a decreased retention time from the site of DNA damage induced single-stranded breaks (84,85). Furthermore, the amino acid substitutions within the central DNA binding domain (219-415 aa) encompassing the first BRCT domain of XRCC1 have been found to disrupt DNA binding in vitro and the recruitment of XRCC1 to near-UV micro-irradiated sites of the nuclei is strongly influenced by the region encompassing amino acids 166 to 310 without affecting its initial recruitment, suggesting that the DNA-binding activity of XRCC1 is crucial for efficient DNA damage repair (86).…”
Section: Discussionsupporting
confidence: 93%
“…However, it should be noted that the fulllength XRCC1 proteins containing either of these mutations were recruited to sites of DNA damage induced by laser microirradiation with similar kinetics to the WT protein (Fig. 7C), although the R280H variant has previously been shown to dissociate more rapidly than WT XRCC1 from sites of DNA damage induced by micro-irradiation (39).…”
Section: Interactions Of Xrcc1 Fragments With Dnamentioning
confidence: 85%
“…Human cells that have lower levels of XRCC1 show significant sensitivity to DNA damaging agents like methyl methanesulfonate (MMS), poly(ADP-ribose) polymerase (PARP) inhibitors, and other DNA damage response and repair inhibitors [ 10 , 11 , 12 , 13 , 14 ]. Additionally, mutations in XRCC1 that reduce its ability to bind PARP1, POLβ, or interact with DNA have been shown to increase hypersensitivity to DNA damaging agents and increase genomic instability and chromosomal aberrations, promoting transformation [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. While several single nucleotide polymorphisms, R399Q and R280H, have been correlated with cancer risk, variations in the gene and protein expression levels of XRCC1 are more commonly noted, particularly in ovarian, breast, and gastric cancers [ 14 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%